2004
DOI: 10.2174/0929867043364450
|View full text |Cite
|
Sign up to set email alerts
|

6-Oxo-Morphinane Oximes: Pharmacology, Chemistry and Analytical Application

Abstract: The permanent therapeutic importance of morphine derivatives in pain treatment has inspired continual synthetic efforts to modify the rigid pentacyclic systems in search for new selective analgesic agents. As a result, several morphinane oximes have been synthesized recently, which have the additional advantage of possessing an oxime group that can provide a method for selective determination of opiate alkaloids in biological matrices. The oximes of hydrocodone and oxycodone have stronger analgesic effect than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The chemistry of oxime metal complexes is interesting because of these species shows variety of reactivity modes. They have been widely studied in variety of biochemical 5,6 and analytical applications 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of oxime metal complexes is interesting because of these species shows variety of reactivity modes. They have been widely studied in variety of biochemical 5,6 and analytical applications 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported on different synthetical approaches for converting the C-6 carbonyl group in 14-oxygenated- N -methylmorphinan-6-ones (i.e., oxycodone, oxymorphone, dihydromorphinone) into a variety of functionalities, for example hydrazones, oximes, semicarbazone, amino, guanidine, sulfate and amino acid derivatives [ 64 , 65 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Subsequent pharmacological studies showed that such modifications generally do not affect the opioid activities of the ligand, with the resulted compounds being potent antinociceptive agents in rodents with reduced unwanted side effects (i.e., respiratory depression and constipation) [ 61 , 64 , 65 , 72 , 73 , 74 , 78 , 79 ].…”
Section: Modifications In Position 6 Of 14-oxygenated- N -Methylmorphinan-6-ones: Design Synthesis and Sar Studiesmentioning
confidence: 99%
“…12,13 They have also attracted attention due to their possible antimicrobial applications. 14,15 The ortho-hydroxy-aryloximes act as excellent bidentate ligands through the nitrogen and oxygen donor atoms.…”
Section: −9mentioning
confidence: 99%